517 - Informal and Formal Depression Care in Nursing Homes (InFormeD): Study protocol of a six month cohort study to better match treatment with residents. (October 2021) - Declercq, Ine; Leontjevas, Ruslan; Knippenberg, Inge; Van Hooren, Susan; De Vriendt, Patricia; Gerritsen, Debby
Abstract: Background: Depression is common among nursing home residents and has a considerable impact on their quality of life. Therefore, there has been an increased interest in interventions aiming at the reduction of depression among nursing home residents. These interventions could be categorized into formal and informal depression care. Formal care includes psychosocial, psychotherapeutic and/or (neuro-)biological interventions. Informal care can be provided by nursing home staff, alongside the formal care (e.g., letting sunlight into the room when one believes in the positive effects of daylight). Although many studies have been done about depression treatment in nursing homes, there is still a lack of insight into the effectiveness of interventions and how they differ among specific target groups (e.g., residents with cognitive impairment versus residents with physical disabilities). Moreover, research into informal care is rather rare. More insight is needed into the effect of formal and informal depression care and the mutually reinforcing effects of those strategies on nursing home residents. This insight is essential to better match treatments with residents and to provide a more comprehensive approach to counter depression. Objectives: The aim of this study is to gain insight in the use of formal and informal depression care and their associations with depression among nursing home residents. Design: A six month cohort study will be conducted. Method: Residents will be recruited in nursing homes across the Netherlands and Flanders (Belgium). To measure formal and informal care, newly developed tools will be cross-culturally validated: one to assess the provided formal care in nursing homes, two tools for measuring the used informal strategies. Depression outcomes will be measured with the Geriatric Depression Scale, Cornell Scale for Depression in Dementia, and the Nijmegen-Observer-Rated Depression-scale). Baseline measurements and cross- sectional analyses will be performed and repeated after six months. The intended associations will be assessed using multiple regression analysis. Conclusion: To develop a good depression care policy, a more comprehensive approach is needed and may benefit both residents and staff.